Multi-wavelength observations of the narrow-line Seyfert 1 galaxy RX J2314.9+2243. Issue Volume 10:Issue S312(2014) (7th March 2016) - Komossa, S.; Myserlis, I.; Fuhrmann, L.; Xu, D.; Grupe, D.; Fan, Z.; Yao, S.; Angelakis, E.; Karamanavis, V.; Zensus, J. A.; Yuan, W.
Abstract: Narrow-line Seyfert 1 (NLS1) galaxies are a sub-class of active galactic nuclei (AGN) with relatively low-mass black holes, accreting near the Eddington rate. A small fraction of them is radio-loud and harbors relativistic jets. As a class, these provide us with new insights into the cause(s) of radio-loudness, the blazar phenomenon at low black hole masses, and the operation of radio-mode feedback. The NLS1 galaxy RXJ2314.9+2243 is remarkable for its multi-wavelength properties. We present new radio observations taken at Effelsberg, and a summary of the recent results from our multi-wavelength study. RXJ2314.9+2243 is radio-loud, luminous in the infrared, has a flat X-ray spectrum and peculiar UV spectrum, and hosts an exceptionally broad and blueshifted [OIII]λ5007 emission line, indicating the presence of a strong outflow. RXJ2314.9+2243 likely represents an extreme case of AGN induced feedback in the local universe.